Identification of Organic Explosives Clues Post-Explosion by GC-MS And GC-NPD Methods - Arce-Rubí, Stephanie (2020)
Methods for the identification of explosives by means of Gas Chromatography Mass Spectrometry (GC-MS) and Gas Chromatography with Nitrogen Phosphorus Detectors (GC-NPD) were implemented and validated. The methods established included the analysis of the following explosive substances: TNT, TNB, 2,4-DNT, 2,6-DNT, 2-NT, 3-NT, 4-NT, PETN, NG, RDX and tetril. For each analyte, the detection limit, the variability in retention time for each analyte, in terms of repeatability and intermediate precision were evaluated by using both chromatography techniques. By means of GC-MS the correlations found between the mass spectrum of the standards and those of the analytes went over 90% for the majority of the nitrotoluenes and for some stabilizers of smoke-free gunpowder. The GC-NPD analysis is an alternative method for the identification of the same analytes done by using GC-MS, with the only exceptions of PETN and 1,3,5 -TBN. The detection limits of these two compounds were inferior with respect to the ones reached by GC-MS. Finally, veracity and effectiveness for both methods were proven by analysing post-explosion samples of six explosive materials. All the explosion events were developed under controlled situations. The samples were extracted through organic solvents; then they were analysed by TLC, GC-MS and GC-NDP. This methods allowed the identification at least of one explosive component in the majority of the samples (83%).